2021
DOI: 10.1101/2021.05.21.445166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cap-dependent translation initiation monitored in living cells

Abstract: Despite extensive biochemical, genetic, and structural studies, a complete understanding of mRNA translation initiation is still lacking. Imaging methodologies able to resolve the binding dynamics of translation factors at single-cell and single-molecule resolution are necessary to fully elucidate regulation of this paramount process. We fused tags suitable for live imaging to eIF4E, eIF4G1 and 4E-BP1 without affecting their function. We combined Fluorescence Correlation Spectroscopy (FCS) and Single-Particle … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Notably, autocorrelations for single JF646 SNAPf-eIF4G and JF585 Halo-eIF4E signals demonstrated that their diffusion only marginally slowed in the cytoplasm of cells treated with SBI-756 or SBI-0498 relative to control cells ( Figure 4C ), suggesting that in cellula SBI-756 and SBI-0498 inhibit eIF4E:eIF4G binding without triggering their dissociation from mRNA. On the other hand, autocorrelation obtained in SBI-5844 treated cells, demonstrated that cytoplasmic JF585 Halo-eIF4E molecules diffuse as fast as their nuclear counterparts ( Figure 4C , right panel), mirroring diffusion of free-eIF4E molecules that do not bind the 5′cap ( Gandin et al, 2021 ), suggesting that in cellula SBI-5844 can dissociate mRNAs from the eIF4F complex.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Notably, autocorrelations for single JF646 SNAPf-eIF4G and JF585 Halo-eIF4E signals demonstrated that their diffusion only marginally slowed in the cytoplasm of cells treated with SBI-756 or SBI-0498 relative to control cells ( Figure 4C ), suggesting that in cellula SBI-756 and SBI-0498 inhibit eIF4E:eIF4G binding without triggering their dissociation from mRNA. On the other hand, autocorrelation obtained in SBI-5844 treated cells, demonstrated that cytoplasmic JF585 Halo-eIF4E molecules diffuse as fast as their nuclear counterparts ( Figure 4C , right panel), mirroring diffusion of free-eIF4E molecules that do not bind the 5′cap ( Gandin et al, 2021 ), suggesting that in cellula SBI-5844 can dissociate mRNAs from the eIF4F complex.…”
Section: Resultsmentioning
confidence: 97%
“…Because the fluorescent signal is recorded simultaneously, the cross-correlation is a direct indication of the concomitant movement and so interaction of the two molecules as they transit through the focal volume ( Kim et al, 2007 ). FCS and FCCS allow us to detect in real-time translation initiation events in living cells since it can resolve unbound initiation factors (fast diffusion) or mRNA bound (slow diffusion) ( Gandin et al, 2021 ). Halo- and SNAP f -tag suitable for live cell imaging, were fused eIF4E and eIF4G respectively without perturbing their function ( Gandin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations